Size effect on void coalescence under intense shear - Xiao, Y.; Nielsen, K.L.; Niordson, C.F. (European journal of mechanics, A, Solids, 2021)
Void interaction, leading to coalescence, is the mechanism leading to ductile failure under intense shearing. Published unit cell model studies have demonstrated that micron-size voids collapse to form micro-cracks while continuous elongation and rotation of the voids thin the intervoid ligaments. At a final stage, the deformation leads to plastic flow localization in the ligament, and the material loses the load-carrying capacity. The micro-mechanism of void collapse, elongation, and rotation has been studied using 2D and 3D unit cell simulations but only within a conventional strain hardening material and, thereby, not accounting for micron scale size effects. However, the severe plastic deformation near the voids implies the development of significant plastic strain gradients, which must be accommodated by geometrically necessary dislocations (GNDs) that strengthens the matrix locally and elevates the stress level. The present research accounts for such gradient strengthening within the matrix in order to investigate the material size effect in ductile shear failure. The work presented leans on the unit cell model approach by Tvergaard (2009), but enables a constitutive length parameter to enter the analysis by substituting the matrix with a Fleck–Willis gradient enhanced material. The results reflect the combined effect of applied load, strain hardening, initial void volume fraction, and microstructure size. The general conclusion is that matrix strengthening, governed by size, delays the loss of load-carrying capacity and leads to less concentrated localization around small void. The results also show that the void collapse, elongation, and rotation mechanism is more sensitive to changes to the applied load, hardening, and initial void volume fraction at small scales. •The size-effect study on void coalescence presents “smaller is stronger” effect.•The ductility increases with diminishing microstructure size.•The peak load carried by the material increases at the micron-scale.•The effect of the loading ratio is less pronounced when down-scaling the microstructures size.